In vitro fertilization postmortem - Patricia Sánchez Ruiz; Nerea Martínez Castellón; Eloísa Fernández Ordóñez (Universidad de Alicante, 2018)
Postmortem IVF is a technique by semen is extracted from the deceased man to fertilize the egg of his wife. The objective of this review of the literature is to know and compare the different options of postmortem IVF in several countries. Methodology: literature review in different databases that return a search in English or Spanish with high relevance with the subject to be treated and available in full text as inclusion criteria, being the absence of any of the above exclusion criteria. Outcome: Currently in Spain it is allowed to perform this technique with a number of requirements and under legal conditions, however in other countries there is a lot of discrepancy, some are not allowed to use this technique under any concept, while in others access She is free for every widow woman who wants it within the first hours of the man's death. Discussion: Few countries have a current legislation on postmortem IVF, and very few countries allow the technique to be performed, even with the authorization of the male prior to death. Conclusions: There is a lot of controversy about the legislation in the different countries, so a deeper investigation on this topic would be necessary.